2014
DOI: 10.5539/ies.v7n2p75
|View full text |Cite
|
Sign up to set email alerts
|

The Indicating Factors of Oral Reading Fluency of Monolingual and Bilingual Children in Egypt

Abstract: This study examined oral reading fluency (ORF) of bilingual and monolingual students. The author selected a sample of 510 (258 males and 252 females) native Arabic-speaking sixth-graders (62 bilinguals and 448 monolinguals) in Egypt. The purposes were; (a) to examine oral reading rate, oral reading accuracy, prosody, and oral reading comprehension as indicating factors in ORF, and b) to investigate the impact of bilingual education on students' ORF in Arabic. Participants individually completed the author-deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 77 publications
(79 reference statements)
2
15
0
Order By: Relevance
“…The only comparable data is that of Hussien, 53 which showed a median oral reading rate of 90 WPM in 6th grade children. The obvious reason for the higher reading rate in Husseins's study is the higher grade levels of the children (6th versus 3rd grade readers).…”
Section: Discussionmentioning
confidence: 99%
“…The only comparable data is that of Hussien, 53 which showed a median oral reading rate of 90 WPM in 6th grade children. The obvious reason for the higher reading rate in Husseins's study is the higher grade levels of the children (6th versus 3rd grade readers).…”
Section: Discussionmentioning
confidence: 99%
“…3, No. 1;2014 Answering the last key question of the current study "What is the effect of the genre (informational and poetic) on oral reading rate, oral reading accuracy and oral reading comprehension of the fifth and tenth grade students?" A Paired-Samples T Test was used as explained in Table 2.…”
Section: Resultsmentioning
confidence: 98%
“…3, No. 1;2014 Latin orthographies, usually English, which makes the science of reading at most the science of reading English (Perfetti & Cao, 2013, p. 5). As consequences, reading research has limited relevance and implications for a universal science of reading (Share, 2008, p. 584).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, there is no adequate research on this topic. Noting the limitation in the literature review for this study, the studies of Hussien (2014aHussien ( , 2014b should be mentioned. Hussien examined the language performance of bilingual children in both Arabic and English and concluded that they performed better than their monolingual counterparts (2014a) and that learning English has a positive effect on their Arabic skills (2014b).…”
Section: Literature Reviewmentioning
confidence: 99%